Burnt-Bricks Production Using Extracted Finer Particles from Soil with Fly Ash Addition - Malkanthi, S.N.; A.A.D.A.J., Perera; Galabada, Harsha; Dharmarathna, P.D. (International Journal of Sustainable Construction Engineering and Technology, 2023)
Earthen building materials, including mud, adobe, rammed earth, and bricks, have a long history of use in civil engineering construction all throughout the world. Burnt bricks are one of these materials that is important. However, the availability of raw materials for making bricks is limited. As a result, numerous alternatives have been investigated as raw materials for making bricks. These substitutes include fly ash, rice husk and ash, industrial, and agricultural waste. The current study suggests a novel method for producing burnt bricks using extracted finer and fly ash. Finer particle extraction was done through soil washing. Since the extracted finer is having high plasticity index and high linear shrinkage, extracted finer was mixed with 20%, 25%, 30%, 40% and 50% fly ash. Fly ash is an industrial waste; hence the use of fly ash for this kind of production would give a sustainable solution for waste management. Every finer-fly ash combination underwent an Atterburg test to evaluate its qualities, particularly its plasticity index and linear shrinkage. Standard-type mold (220 x 115 x 75 mm) was used to produce the handmade bricks. Compressive strength, flexural strength, water absorption, density, and dimension variations of burned bricks were all examined. Results were compared with SLS 39: Specification for burnt clay bricks. Further, these properties were compared with the same properties of bricks made with soil taken from the brick-making industry mixed with fly ash and industrial available burnt-bricks. Additionally, wire-cut bricks were produced using extracted finer and 25% fly ash. The dimensional variation of finer-fly ash mixed burnt bricks is decreasing when the fly ash % is increased relative to the mold size. Compressive strength of the Grade 2 category was demonstrated using bricks manufactured with a 25% fly addition, according to SLS 39. According to the aforementioned findings, burnt bricks composed of extracted finer and fly ash have higher desirable qualities when 25% more fly ash is added. Additionally, it shows that using fly ash results in lightweight bricks. The wire-cut bricks made with this selected mixture give 10.64 N/mm2 of compressive strength and it satisfies the SLS 39 requirements for wire-cut bricks. Also, its water absorption was nearly 16% which is below the SLS required value (18%).